Transmission of Sentenced Persons in International Conventions, with a Glance at Islamic Jurisprudence - hassan Porbafrani; Ahsan aknarifard; Hassan Badri (پژوهش تطبیقی حقوق اسلام و غرب, 2015)
The protocol of transmission of sentenced persons is one new concept in the field of International Criminal Law. Under some conditions, sentenced person with an irrevocable judgment in a foreign country may be delivered to his or her country. In this case, having recognized its validity and consequences, the national government implements that judgment. By transition of this prisoner to his or her country, the rehabilitative costs will reduce and the effects are performed better, while at the same time human rights is also being observed. Notwithstanding these advantages and disadvantages, Iran has signed this transmission protocol with only ten countries. International Treaties on the transmission of sentenced persons is not against the Islamic jurisprudence.